Efektifitas Program Tax Amnesty dan Faktor Keberhasilannya: Pembelajaran dari Negara-Negara yang Pernah Menerapkan - Safri Safri (JURNAL MITRA MANAJEMEN, 2016)
ABSTRACTState needs the extra revenue to cover the budget shortfall is the basis of the implementation of the amnesty, if it is a short-term goal, the tax amnesty is not an important part and reform.Of the 240 million population of Indonesia, the number of registered taxpayers are still less than 30 million people, and of that number, only a third of that reported income tax returns in 2015, or less than 10 million inhabitants, or only 0.04% of taxpayers who already reported SPT Income Tax, 2015.Naturally Indonesia should be filled to the countries that are successful in the implementation of the amnesty, so expect the tax amnesty to three times this will be successful, and there will be no tax amnesty in the future. Keywords: Tax Amnesty, SPT Income TaxEfektifitas Program Tax Amnesty dan Faktor Keberhasilannya: Pembelajaran dari Negara-Negara yang Pernah Menerapkan